Loyalty and identity: Jacobites at home and abroad - Monod, Paul Kléber; Pittock, Murray; Szechi, D. (Studies in modern history, 2010)
"This collection of essays provides a series of fresh approaches to a fascinating subject: Jacobitism. The contributors focus on issues of identity and memory among Jacobites in Scotland, Ireland, England and Europe. They examine Jacobitism as an integral aspect of culture and society in the British Isles and beyond during the century after 1688"--Provided by publisher